2021
DOI: 10.1186/s40662-021-00241-7
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical changes in allergic conjunctivitis

Abstract: Background To explore corneal biomechanical changes, identify related factors and determine early indicators of keratoconus (KC) development risk in allergic conjunctivitis (AC) patients. Methods A total of 50 patients, including 20 eyes without AC and 30 eyes with AC were enrolled in this study. All patients underwent a complete ocular examination, including evaluations of clinical manifestations of AC, corneal tomography and densitometry by Penta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…Therefore, among the parameters evaluated in their study, posterior corneal elevation changes were identified as the earliest sign of subclinical KC ( 15 , 16 ). Additionally, in our study, we found that the increased elevations of both the anterior and posterior corneal surfaces were positively correlated with altered TBI, which was identified as a sensitive indicator of KC development risk in AC patients in our previous study ( 19 ). This result to a certain extent demonstrates the possibility and risk of KC occurrence in AC patients.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Therefore, among the parameters evaluated in their study, posterior corneal elevation changes were identified as the earliest sign of subclinical KC ( 15 , 16 ). Additionally, in our study, we found that the increased elevations of both the anterior and posterior corneal surfaces were positively correlated with altered TBI, which was identified as a sensitive indicator of KC development risk in AC patients in our previous study ( 19 ). This result to a certain extent demonstrates the possibility and risk of KC occurrence in AC patients.…”
Section: Discussionsupporting
confidence: 70%
“…However, sensitive indicators for screening AC patients at high risk of developing KC are still under investigation. In our previous study, we showed that TBI could be used as an indicator of KC development risk in AC patients ( 19 ). In the current study, we found that both the anterior and posterior corneal elevation values were significantly higher in AC patients than in normal subjects and were further identified to positively correlate with the altered TBI in AC patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations